The Effect of Work Environment and Work-Life Balance on Job Satisfaction and Organizational Commitment in Millennial Employees - Nia Kusuma Wardhani; Anees Janee Ali (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
The dynamics of work environment, work-life balance, job satisfaction, and organizational commitment are critical in shaping employee performance, especially among millennials who prioritize both career growth and personal well-being. This study aims to examine the influence of work environment and work-life balance on job satisfaction and organizational commitment. A quantitative approach was employed, surveying millennial employees in West Jakarta. Data were analyzed using structural equation modeling to assess direct and indirect effects. The results reveal that both work environment and work-life balance significantly affect job satisfaction, while job satisfaction strongly predicts organizational commitment. In contrast, work environment and work-life balance do not directly influence organizational commitment. These findings underscore that supportive work environments and balanced work-life practices alone may not guarantee organizational commitment unless they enhance job satisfaction. The study suggests that organizations seeking to retain millennial talent should prioritize strategies that foster both satisfaction and engagement, including workplace design, supportive policies, and career development opportunities, by emphasizing job satisfaction as the central link between workplace conditions and commitment.